2006
DOI: 10.1002/adsc.200505411
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Arenes with Benzylic and Propargylic Alcohols – Classical versus Fancy Catalysts

Abstract: Gold chloride and BF 3 · etherate were tested as Friedel-Crafts catalysts in the propargylation of electron-rich arenes: differences in reactivity of the catalysts can be used to achieve high selectivity either for monoalkylation or for multiple alkylation products. In the case of a macrocyclization towards a heterocalixarene, gold catalysts exhibited a pronounced selectivity, whereas p-toluenesulfonic acid as catalyst opened up a competing pathway to a structural isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 24 publications
(10 reference statements)
1
48
0
2
Order By: Relevance
“…Quite interestingly, different selectivity is obtained as a function of the Lewis acid catalyst. [109] Prim and Campagne described the direct amination of benzylic alcohols 1 and 2 with Boc-amine, tosylamine, nitroaniline, and TMSN 3 in the presence of NaAuCl 4 (5 mol-%) as catalyst in CH 2 Cl 2 at room temperature. Generally, the workup of the reaction comprised filtration through a silica pad to give the corresponding benzylic amine in analytically pure form.…”
Section: Gold Complexesmentioning
confidence: 99%
“…Quite interestingly, different selectivity is obtained as a function of the Lewis acid catalyst. [109] Prim and Campagne described the direct amination of benzylic alcohols 1 and 2 with Boc-amine, tosylamine, nitroaniline, and TMSN 3 in the presence of NaAuCl 4 (5 mol-%) as catalyst in CH 2 Cl 2 at room temperature. Generally, the workup of the reaction comprised filtration through a silica pad to give the corresponding benzylic amine in analytically pure form.…”
Section: Gold Complexesmentioning
confidence: 99%
“…Dyker and co-workers used AuCl 3 for the efficient propargylation of electron-rich arenes. [11] Further catalytic methodologies [12] for the propargylic substitution take use of ruthenium [13], rhenium [14], bismuth [15], or copper [16] catalysts. Simple Brønsted-acids such as p-toluenesulfonic acid were also found to catalyze the direct substitution of the hydroxyl group in propargylic alcohols [17].…”
Section: Resultsmentioning
confidence: 99%
“…This electrophile 7 appears to be one of the synthetically most useful building blocks tested in the earlier series (5,(7)(8)(9)(10)(11), exhibiting a high diastereoselectivity for an otherwise difficult selective b-arylation of a carboxylate. We were delighted to note that the functional group tolerance of the catalyst was perfectly corroborated by these studies as was the previously observed diastereoselectivity.…”
Section: Variation Of the Arene Nucleophilementioning
confidence: 96%
“…Highly effective Lewis acids have been found which catalyze cleanly the reaction of various arenes with alcohols [3] and acetates. [4] The use of gold-A C H T U N G T R E N N U N G (III) chloride [5] for the catalytic Friedel-Crafts alkylation with benzylic acetates as described by Beller et al [6] and with benzylic alcohols as described by Dyker et al [7] is of particular relevance to the present work. [8] Hashmi et al [9] compared the reactivity of AuCl 3 with other catalysts for use in the condensation of carbonyl compounds with electron-rich arenes.…”
Section: Introductionmentioning
confidence: 99%